USAGE OF SOCIAL MEDIA MARKETING IN TOURISM - Popović, Milica (The Business of Tourism, 2022)
Nowadays, the usage of social media has become integral part of life for many generations. These web-based tools allowed tourism companies to identify tourists’ needs and remain competent on ever-changing market. Thus, this research paper presents the application of social media in tourism marketing, whereby extending tourism boundaries in innovative way. In this regard, the subject of the paper is to determine if social media has positive impact on business performances in tourism sector and how to incorporate these tools in tourism brand strategies. The paper is based on secondary data, gathered from academic publications from different scientific fields: tourism, marketing and IT. Research results confirmed the primary hypothesis, which indicated that social media has positive impacts on tourists’ purchase intentions and brand loyalty, through which business performances of tourism companies have been improved. The significance of the research results is reflected as a optimization of social media usage in tourism marketing in order to improve the quality of tourism services and tourists’ satisfaction.
Keywords: tourism; marketing; social media; brand; buying intention